Enterprise Interoperability II New Challenges and Approaches - Jardim-Gonçalves, Ricardo; Müller, Jörg; Mertins, Kai; Zelm, Martin (Proceedings of the I-ESA Conferences,, 2007)
Interoperability: the ability of a system or a product to work with other systems or products without special effort from the user is a key issue in manufacturing and industrial enterprise generally. It is fundamental to the production of goods and services quickly and at low cost at the same time as maintaining levels of quality and customisation. Interoperability is achieved if internal and external collaborators can interact on at least three levels: data, applications and business enterprise (through the architecture of an enterprise model and making allowance for the semantics of both partners). Not only a problem of software and IT technologies, it implies support for communication and transactions between different organisations that must be based on shared business references. Today, a new and important consideration must be taken into account - economic business evaluation and the definition of dissemination policy. Composed of over 90 papers, Enterprise Interoperability II ranges from academic research through case studies to industrial and administrative experience of interoperability. The international nature of the authorship continues to broaden. Many of the papers have examples and illustrations calculated to deepen understanding and generate new ideas. The I-ESA'07 conference from which this book is drawn was sponsored by the European Union via the INTEROP network of excellence and the ATHENA integrated project (in the frame of the 6th IST Framework Research Program). It is also supported by the International Federation for Information Processing, the International Federation of Automatic Control and various national associations. A concise reference to the state of the art in software interoperability, Enterprise Interoperability II will be of great value to engineers and computer scientists working in manufacturing and other process industries and to software engineers and electronic and manufacturing engineers working in the academic environment.